Hourly streamflow forecasting with ARMA models for maximizing hydropower revenues - Rodero, Augusto O. (2010)
Hydrologic streamflow forecasting has always been a concern for water resources engineers for optimal operations of water systems. The autoregressive - moving average (ARMA) models is a group of stochastic models popularly used by modelers over the past decades as a tool for streamflow forecasting.